Can pelvic organ prolapse in postmenopausal women be treated with laser therapy?. (2nd January 2021) - Athanasiou, S.; Pitsouni, E.; Cardozo, L.; Zacharakis, D.; Petrakis, E.; Loutradis, D.; Grigoriadis, T.
Abstract: Purpose: This study aims to assess the effectiveness of the non-ablative photothermal erbium laser (Er:YAG laser) for managing anterior and/or posterior vaginal compartment prolapse. Methods: A randomized, single-blind, 1:1 trial was performed comparing Er:YAG laser treatment to watchful waiting in postmenopausal women with symptomatic cystocele and/or rectocele stage 2 or 3 who opted to undergo surgery due to bothersome prolapse symptoms. Three Er:YAG laser treatments at monthly intervals were applied for the Er:YAG laser group, while there was no treatment for the watchful-waiting group. The primary outcome was the proportion of patients with stage 0 or 1 following laser treatment, while secondary outcomes included the Pelvic Organ Prolapse Quantification System (POP-Q points), Pelvic Floor Distress Inventory Questionnaire short-form, Pelvic Floor Impact Questionnaire short-form, and Patients Global Impression of Improvement (PGI-I). All outcomes were evaluated at baseline and 4 months post baseline. Results: Thirty women (15 vs. 15) were eligible to be included. No participants (0%) in either group had POP-Q stage 0 or 1 at 4 months. Moreover, no change was present in the secondary outcomes. In the PGI-I, 2/15 (14%) and 0/15 (0%) participants declared much better/very much better in the laser and watchful-waiting group, respectively. Conclusions: The findings of this study do not support use of the intravaginal Er:YAG laser for treatment of the anterior/posterior vaginal wall. Clinical trial identification number: NCT03714607